Kazakhstan and Eastern Turkestan in the 17th – 19th centuries from the history of political interaction - Karimova, Р.У.; Massimova, Х.В.; Karimova, З.К. (Journal of Oriental Studies, 2024)
The article explores the interrelations of two adjacent subregions of Central Asia - Kazakhstan and Eastern Turkestan in the 17th - 19th centuries. The research aims to identify the political interaction between Kazakhstan and Eastern Turkestan and its evolution in historical retrospect. The study is based on a scholarly foundation formed through comparative analysis of Chinese and Turkic sources, archival materials, and data from specialized literature. The methodology of comparativism provided an opportunity to examine historical events in the context of geopolitical interests of major powers in Central Asia - the Qing and Russian empires. A significant methodological approach involved studying the history of Kazakhstan and Eastern Turkestan based on the extensive utilization of local understudied sources. The analysis of the materials provided an opportunity to demonstrate the history of interaction between Kazakhstan and Eastern Turkestan within the accepted chronological framework and its changes depending on the political context. The 17th to 19th centuries were rich in events for the studied sub-regions, playing a pivotal role in their subsequent fate. From international and generally allied relations between the two sovereign states in the 17th century, they evolved with the establishment of the Russian Empire's protectorate over the Kazakh hordes and the conquest of Eastern Turkestan by the Qing Empire, becoming purely interethnic in nature. The external politics during this period came under the authority of the metropolises. The close connection between the ethnicities inhabiting the sub-regions was further strengthened by common origins, related languages, a shared religion, cultural traditions, and the dramatic nature of the established situation. This connection manifested not only in established economic and cultural ties and trade exchange but primarily in common political interests, emerging during periods of national liberation struggle. Key words: Kazakhstan, East Turkestan, history, political interaction, interethnic relations.